Characterizing Thermal, Acoustic, Water Absorption, and Flammability Performance of Pineapple Leaf Fibre Insulation: A Sustainable Alternative for Building Applications - Muhammad Nazrin Zamri; Razali, Mohd Azahari; Mohd Nor, Norfakhira; Nur Syafiqah Adha Narrudin; Masataro Suzuki; Mohd Azni Md Kasim (Journal of Advanced Mechanical Engineering Applications, 2026)
The sustainable usage of pineapple leaf fibre (PALF) for insulation applications on building components was studied. To prepare one-layer, two-layer and three-layer insulation samples, they have been cleaned, treated with alkali, ground, moulded and dried. Thermal, Acoustic, Water absorption and Flammability tests were performed on fabricated samples. The results indicated that the thickness of the layers increased, the insulation performance improved generally. The 3 layer configuration showed the best thermal performance with an average temperature difference of 0.56°C and the best acoustic performance with an average sound reduction of 14.37 dB. The three-layer sample had the longest ignition time of 67.67 s and shortest smouldering length of 2.0 cm in the flammability test, which meant that the sample had a better flammability resistance. The water absorption increased as the insulation thickness increased, the three-layer sample has the highest water absorption value of 37.90%. Comparative performance assessment with the conventional insulation material showed that PALF insulation has the competitive performance in terms of thermal and acoustics properties and has the superior performance in terms of sustainability and environmental benefits. The results showed that pineapple leaf fibre is an environmentally friendly alternative building materials insulation.